2000
DOI: 10.1080/j.1600-0412.2000.079001003.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal fibronectin as a predictor of term labor: A literature review

Abstract: Determining the presence of FFN in cervicovaginal secretions promises to provide an indicator relating to the prediction of term labor, as well as to the prediction of successful labor induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…FFN may be released into cervicovaginal secretions through mechanical and infection‐mediated damage to the foetal membranes or placenta prior to birth . Elevated FFN levels in cervical fluids indicate an increased likelihood of delivery; thus, they are a predictor of term and preterm birth . Unlike in experimental animals such as sheep and small rodents, in human pregnancy blood levels of progesterone increase rather than decrease during labour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FFN may be released into cervicovaginal secretions through mechanical and infection‐mediated damage to the foetal membranes or placenta prior to birth . Elevated FFN levels in cervical fluids indicate an increased likelihood of delivery; thus, they are a predictor of term and preterm birth . Unlike in experimental animals such as sheep and small rodents, in human pregnancy blood levels of progesterone increase rather than decrease during labour.…”
Section: Introductionmentioning
confidence: 99%
“…Several proteomic studies have reported biomarkers of term and preterm births . Over a hundred biomarkers of spontaneous preterm birth have been identified for various types of biochemical pathways .…”
Section: Introductionmentioning
confidence: 99%
“…11 A review of eight reports concluded that a positive fFN was associated with significantly shorter delivery intervals than when a negative fFN result is obtained. 12 A positive fFN can aid management by predicting the onset of spontaneous labor within days, so that the patient can be counseled to wait. On the contrary, a negative fFN with a poor bishop's score can defer an induction in the absence of an emergent indication.…”
Section: Fetal Fibronectinmentioning
confidence: 99%
“…Maternal immunomodulation in particular is vital to the tolerance of antigens of paternal origin [1][2][3][4]. Increased corticotrophin-releasing hormone in maternal plasma and secretion of fetal fibronectin into cervicovaginal fluids are indicators of delivery [5,6]. However, the timing of human labor, particularly the changes at the molecular level resulting in labor, are not currently understood.…”
Section: Introductionmentioning
confidence: 99%